A variedade andina do espanhol vs. o centro-norte peninsular: atitudes e crenças dos asturianos - Pérez-Rodríguez, Marisela del Carmen (2025)
The purpose of this article is to analyze the perception of Asturians towards the Andean variety of Spanish, based on the responses obtained in the second phase of PRECAVES XXI (Project for the Study of Beliefs and Attitudes towards the Varieties of Spanish in the 21st Century). A total of 108 respondents, evenly distributed by sex, age and educational level, were analyzed. In this variety, the percentage of correct identification is lower with respect to the varieties of peninsular Spanish.  The results suggest that for Asturians the Andean variety is fundamentally clear and pleasant. The best and worst valued features are the phonic ones. The region and the country are valued as “nice” and “interesting”. The interviewees recognize that it is a different variety, although they value positively that it is a conservative variety, like their own.